Tempos de crise: o império português, a crise açucareira, o tráfico de escravos e a lei das arqueações (1640-1695) - Salles, Wesley Dartagnan [UNESP] (2014)
This paper aims to study the Portuguese legislation on the slave trade between Angola and the State of Brazil. Thus, we observed that slaver legislation between 1640 and 1695 had the main purpose of assisting the sugar production. The tonnage of law of 1684 was the principal representation of these aspects. We conclude that the law of 1684 was a response to the problems of Brazil, specifically the sugar crisis that began between the 60s and 70s. We conclude, on the other hand, the law sought to ensure Angola's monopoly of slave exports, to the detriment of the rise of the Costa da Mina